Exploring the Effectiveness of Narrative Therapy AmongProlonged Grief Disorder (Journal of Asian Development Studies, 2024)
According to WHO, Prolonged Grief Disorder (PGD)is a potentially disabling condition thataffects approximately 10% of suffering people. Narrative therapy is effective in treating prolongedgrief disorder. This study aimed to investigate the efficacy of narrative therapy for those sufferingfrom prolonged grief disorder. Data was collected by using semi-structured interviews consistingof four therapy sessions over a follow-up of four months using a qualitative research methodologywith two participants who were purposefully sampled and had been diagnosed with prolongedgrief disorder. Both clients showed improvement after four follow-up sessions. Client 1 reportedgood progress, showing the core narratives of loss, emotional regulation, and positivetransformation. In the process of externalization techniques and homework, such as letter writing,she reported having better emotional health or a new perspective. Client 2 also reported to havebenefited from the therapy, but she had faced more profound challenges, such as self-blame andsuicidal ideation, requiring psychiatric referral. The outcomes demonstrated that narrativetherapy is very effective in managing prolonged grief disorder.